1979
DOI: 10.1161/01.res.45.3.420
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in left ventricular regional dimensions and function during chronic volume overloading in the conscious dog.

Abstract: SUMMARY As the left ventricle dilates during chronic volume overloading, it assumes a more spherical configuration, suggesting a nonuniform regional myocardial response. Accordingly, we studied early alterations in left ventricular geometry and regional function induced by chronic volume overloading in the canine heart subjected to an aortocaval fistula. Nine mongrel dogs were instrumented with ultrasonic crystal pairs placed perpendicularly to the long axis to measure instantaneous segment lengths in the apic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 39 publications
(27 reference statements)
1
15
0
Order By: Relevance
“…Studies of several forms of myocardial and valvular disease have revealed abnormalities of dynamic shape deformation. 8 " 12 These and other data have shown that the larger the ventricular chamber volume the rounder the shape and that when the percent of volume ejected is reduced, dynamic shape change is similarly decreased. 8" 1013 The data, however, have not demonstrated that dynamic shape change abnormalities are in any sense separable from volume change, nor have they been consistent about the nature of these abnormalities.…”
mentioning
confidence: 64%
“…Studies of several forms of myocardial and valvular disease have revealed abnormalities of dynamic shape deformation. 8 " 12 These and other data have shown that the larger the ventricular chamber volume the rounder the shape and that when the percent of volume ejected is reduced, dynamic shape change is similarly decreased. 8" 1013 The data, however, have not demonstrated that dynamic shape change abnormalities are in any sense separable from volume change, nor have they been consistent about the nature of these abnormalities.…”
mentioning
confidence: 64%
“…from the difficulty in longitudinally measuring contractile function in humans (where a contractility deficit is known to occur) and also from the fact that few experimental models of volume overload (where contractile function could be studied longitudinally) consistently produced contractile dysfunction (33)(34)(35)(36)(37)(38) Limitations to assessment of contractile function. A key premise of our study is that we are able to measure contractile function accurately.…”
Section: Discussionmentioning
confidence: 99%
“…24 In volume overload states, LV dilatation and eccentric hypertrophy are compensatory mechanisms frequently associated with changes in the LV from an ellipsoid to a more-spherical shape. 21,25 Such geometry and loading changes can alter functional evaluation of the LV by classical parameters, such as EF or shortening fraction, 25,26 as well as novel deformation parameters. 21,27 In this study, we performed a comprehensive assessment of the effects of normal pregnancy on LV mechanics using standard and novel morphological and functional echocardiographic parameters while considering LV load and shape.…”
Section: Editorial See P 283 Clinical Perspective On P 297mentioning
confidence: 99%